Ammonia sensing using multilayer graphene grown on Co-Ni/Al2O3 substrate - Ali, May; Abdul Rashid, Suraya; Hamidon, Mohd Nizar; Md. Yasin, Faizah; Al-Sudani, Farah Talib Jasim; Victor, Ayodele Bamidele (2018)
Ammonia is widely employed in several industrial processes such as fertilizer, fire power plant, and food processing. Hence, it is expedient for the detection of ammonia in trace amount which necessitated the use of sensing materials. In this study, multilayer graphene grown on Co-Ni/Al2O3 substrate using Chemical Vapour Deposition at a temperature range of 700-800 °C was employed for gas sensing application at room temperature. The sensitivity of the multilayer graphene to the detection of different concentrations of ammonia as a function of time was investigated. The finding shows that the minimum sensitivity response of the multilayer graphene at 0.06% ammonia concentration was 7.29%, while the maximum sensitivity response of the multilayer at 1% ammonia concentration was 8.3%, which is an indication that the MLG film-based sensor has an affinity towards NH3.